Korelasi Genotipe dan Fenotipe Antar Sifat Kuantitatif Pada Populasi Segregasi Transgresif Kacang Hijau - Julian Timisela; Aca A Anakotta; Adriana Hiariej; Edizon Jambormias (Universitas Pattimura, 2020)
Mung bean (Vigna radiata L. Wilczek) is one of the food plants as a source of vegetable protein for humans. One of these is a population of transgressive segregation resulting from crossing in mung beans. This research aims to estimate the correlation between genotype and phenotype values ​​between quantitative traits in the transgressive segregation population of mung beans. Genetic material was 11 lines of transgressive segregated in the selection generation S2:2 of varieties Mamasa Lere Butnem × Lasafu Lere Butnem crosses. Genotype correlation analysis was obtained from the decomposition of genetic variance components from the results of the analysis of variance according to a randomized complete design with sub-sampling, consisting of 13 genotypes (including check varieties) which were two replications. The results showed a genotype correlation between the quantitative traits of mung beans that indicated the possibility of direct selection of the populations of transgressive segregation lines on yields and indirectly through easily observable traits such as harvest age, number of pods, and number of seeds. Keywords: genetic correlation, mungbeans, quantitative traits ABSTRAK Kacang hijau (Vigna radiata L. Wilczek) merupakan salah satu tanaman pangan sebagai sumber protein nabati bagi manusia. Salah satu diantaranya adalah populasi segregasi transgresif hasil persilangan pada kacang hijau. Penelitian ini bertujuan untuk menduga nilai korelasi genotipe dan fenotipe antar sifat-sifat kuantitatif pada populasi segregasi transgresif kacang hijau. Bahan genetik adalah 11 galur segregan transgresif pada generasi seleksi S2:2 zuriat persilangan varietas Mamasa Lere Butnem × Lasafu Lere Butnem. Analisis korelasi genotipe diperoleh dari penguraian komponen ragam-peragam genetik dari hasil analisis peragam sesuai model acak rancangan acak lengkap dengan anak contoh, terdiri atas 13 genotipe (termasuk varietas penguji) yang diulang dua kali. Hasil penelitian memperlihatkan adanya korelasi genotipe antar sifat-sifat kuantitatif kacang hijau yang mengindikasikan kemungkinan seleksi langsung populasi galur segregasi transgresif terhadap hasil maupun tak-langsung melalui sifat yang mudah diamati seperti umur panen, jumlah polong dan jumlah biji. Kata Kunci: kacang hijau, korelasi genetik, sifat kuantitatif